Reflections and speculations on the progress in Geographic Information Systems (GIS): a geographic perspective. Issue 2 (1st February 2019) - Lü, Guonian; Batty, Michael; Strobl, Josef; Lin, Hui; Zhu, A-Xing; Chen, Min
ABSTRACT: Great strides have been made in Geographic Information Systems (GIS) research over the past half-century. However, this progress has created both opportunities and challenges. From a geographic perspective, certain challenges remain, including the modelling of geographic-featured environments with GIS data model, the enhancement of GIS's analysis functions for comprehensive geographic analysis and achieving human-oriented geographic information presentation. Several basic theoretical and technical ideas that follow the workflow and processes of geographic information induction, geographic scenario modelling, geographic process analysis and geographic environment representation are proposed to fill the gaps between GIS and geography. We also call for designing methods for big geographic data-oriented analysis, making best use of videos and developing virtual geographic scenario-based GIS for further evolution.